University–industry collaboration for BIM education: Lessons learned from a case study. Issue 6 (December 2020) - Chen, Ke; Lu, Weisheng; Wang, Jing
Over the past decade, the global construction industry has shown a clear and urgent need for its professionals to command building information modeling (BIM) knowledge. Many educational institutions have thus incorporated BIM into their construction engineering and management-related programs. However, BIM education faces several challenges, such as the difficulties in transforming existing programs, a lack of instructors with sufficient practical knowledge and misalignment of educational outcomes and industry needs. Many educators thus advocate university–industry collaboration, but this effort is hampered by unanswered questions, including when, what and how both parties can contribute to the collaboration to achieve a win–win situation. This article attempts to answer these key questions in BIM education by relating them to university–industry collaboration in pedagogical design, course delivery and educational outcomes. It does so by conducting a case study whereby the researchers adopted a non-participant observation approach to observe the experience of participants in teaching and learning a BIM course. Feedback from the participants showed that such collaboration could help to narrow the gap between educational outcomes and industry needs. Based on that outcome, another contribution of this research is an analytical framework developed and substantiated to provide a more structured way to guide 'town and gown' collaboration for BIM education.